Characteristics, Models, Strategies and Success of Educational Leadership - Fatnun Fajriyah; Zuhairoh Al Mahfudhoh; Aqwa Kau Kaba (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
Educational leadership is at the core of change and progress in the world of education. This article aims to delve deeper into these concepts. We will outline the characteristics, models, strategies, as well as key factors that form the foundation of successful educational leadership. This research employs a literature review method by gathering relevant literature on educational leadership. Islamic educational leadership is the ability of school principals to influence the actions and thought processes of teachers or staff, both individually and collectively, and instill awareness and a desire to achieve educational goals in accordance with Islamic values. The characteristics of educational leadership are based on the qualities of the Prophet Muhammad, namely truthfulness (shiddiq), trustworthiness (amanah), communication (tabligh), and intelligence (fathanah). Educational leadership strategies encompass aspects of planning, organizing, directing, and supervising. The success of educational leadership is influenced by several factors, including insight and skills, institution or position, personality, and personal attitudes.